Reconciling the apparent absence of a Last Glacial Maximum alpine glacial advance, Yukon Territory, Canada, through cosmogenic beryllium-10 and carbon-14 measurements - B. M. Goehring; B. Menounos; G. Osborn; A. Hawkins; B. Ward (Geochronology, 2022)
We present a new in situ produced cosmogenic beryllium-10 and carbon-14 nuclide chronology from two sets (outer and inner) of alpine glacier moraines from the Grey Hunter massif of southern Yukon Territory, Canada. The chronology of moraines deposited by alpine glaciers outside the limits of the Last Glacial Maximum (LGM) ice sheets potentially provides a less-ambiguous archive of mass balance, and hence climate, than can be inferred from the extents of ice sheets themselves. Results for both nuclides are inconclusive for the outer moraines, with evidence for pre-LGM deposition (beryllium-10) and Holocene deposition (carbon-14). Beryllium-10 results from the inner moraine are suggestive of canonical LGM deposition but with relatively high scatter. Conversely, in situ carbon-14 results from the inner moraines are tightly clustered and suggestive of terminal Younger Dryas deposition. We explore plausible scenarios leading to the observed differences between nuclides and find that the most parsimonious explanation for the outer moraines is that of pre-LGM deposition, but many of the sampled boulder surfaces were not exhumed from within the moraine until the Holocene. Our results thus imply that the inner and outer moraines sampled pre- and post-date the canonical LGM and that moraines dating to the LGM are lacking likely due to overriding by the subsequent Late Glacial/earliest Holocene advance.